Development of overall performance effectiveness in job shop manufacturing process - Teoh, Yong Siang (2018)
Overall equipment effectiveness (OEE) is implemented by the case company, an aerospace part manufacturing company, to encourage machines to operate all the time at the ideal speed and produce no quality defect in extreme case. However, integration between workstations and transporting activities, deviation of production from customer demand, and imbalanced capacity among processes are neglected under OEE implementation. The consequences include inefficient material flow, overproduction and excessive inventory level, as well as lack of interaction between workstations. Therefore, objectives of this study aim to quantify the impact of transportation efficiency onto the workstations, to synchronize capacity available among them and also to monitor the fulfillment of customer demand in terms of delivery time and production amount. The critical measures are shorter lead time and wait time, less throughput, minimal equipment utilization and less capacity incurred. Simulation results have shown that both transportation efficiency and performance of Autoclave workstation affect material flow and throughput rate respectively. Consequently, the performance of workstations they connect with are also affected. Besides, simulation also proves different production rate and imbalanced capacity throughout production system. Therefore, Overall Performance Effectiveness (OPE) is proposed to consider customer demand, historical equipment utilization and Takt time of each workstation. This promotes reasonable utilization of resource to avoid both overprocessing and overproduction issues which are invisible in OEE. Furthermore, delay propagation throughout production system and interrelationship between processes are quantified by delivery performance (DP) of OPE. The waiting time and lead time spent in each workstation are monitored under the DP. Responsibility of all workstations and transportation process in delivering demand on time are quantified. Last but not least, transportation process which serves as the connectors of manufacturing processeses is also quantified and monitored by proposed Transportation Measure (TM). TM aims to reduce the queue length at destination and the corresponding waiting time with reasonable utilization of forklift. It also promotes less capacity investment in transportation and prioritizes its scheduling according to urgency of destination workstation. In short, newly proposed Overall Performance Effectiveness (OPE) and the quantification of Transportation Measure (TM), which affect each other, help in promoting better delivery performance in terms of production amount and lead time. Besides, reasonable utilization equipment and minimal consumption of material are promoted to fulfill the demand. The effectiveness of entire production line is examined as a unity with joint responsibility under varying transportation efficiency and cycle time of each workstation. Both OPE and TM could be implemented together to optimize the production system. All of these are not quantified and provided by the OEE implemented by the case company.